2017
DOI: 10.1111/poms.12750
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Inventory Overstocking: Optimal Order‐up‐to Level to Achieve a Target Fill Rate over a Finite Horizon

Abstract: S ervice level agreements (SLAs) are widely adopted performance-based contracts in operations management practice, and fill rate is the most common performance metric among all the measurements in SLAs. Traditional procedures characterizing the order-up-to level satisfying a specified fill rate implicitly assume an infinite performance review horizon. However, in practice, inventory managers are liable to maintain and report fill rates over a finite performance review horizon. This horizon discrepancy leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Pricing policies can also substantially vary based on the context they are used in. Inventory management is a critical business function for many firms, given that marginal improvements can lead to substantial savings (Tan et al 2017). In short, an inventory-based dynamic pricing policy needs to correspond with ordering and supply decisions, production control and safety stock to hedge potential demand uncertainty (Li et al 2015a).…”
Section: Inventory Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Pricing policies can also substantially vary based on the context they are used in. Inventory management is a critical business function for many firms, given that marginal improvements can lead to substantial savings (Tan et al 2017). In short, an inventory-based dynamic pricing policy needs to correspond with ordering and supply decisions, production control and safety stock to hedge potential demand uncertainty (Li et al 2015a).…”
Section: Inventory Managementmentioning
confidence: 99%
“…Thus, firms are often faced with a trade-off between overstocking and understocking applying markdown programs or low pricing strategies as a way to balance the two sides (Huang et al 2014;Özer and Zheng 2016;Zhang et al 2019). Overstocking, sometimes referred to as 'inventory waste,' creates costs for holding inventory and accounts for lost sales (Huang et al 2014;Tan et al 2017). In this regard, Liu and Van Ryzin (2008) analyze deliberate understocking, which creates rationing risk and is bound to incentivize buyers to purchase earlier and at higher prices.…”
Section: Inventory Managementmentioning
confidence: 99%
“…The most common product availability measure observed in practical settings is the fill‐rate service level (Bijvank, 2014; Teunter et al., 2017; Tan et al., 2017; Babiloni and Guijarro, 2020), defined as the fraction (β) of demand met directly from inventory on hand in any period (Schneider, 1981). However, the most commonly used product availability measure in JLIP is the αL$\alpha _L$ service level, defined as the probability (αL$\alpha _L$) that stockouts do not occur during a replenishment cycle (Schneider, 1981), where L refers to the lead time.…”
Section: Introductionmentioning
confidence: 99%
“…According to several authors (Babiloni and Guijarro [5], Teunter et al [33], Tan et al [29], Bijvank [7]) the β service-level definition is the most observed in practical settings. Consequently, it can be inferred that the size of the stockouts is the most important shortage dimension for inventory managers.…”
Section: Introductionmentioning
confidence: 99%